Catalytic conversion of RBD palm oil to gasoline: the effect of silica-alumina ratio in HZSM-5 - H. K., Farizul (Penerbit UTM Press, 2007)

(untitled)
The RBD palm oil was converted to gasoline by passing its vapor through HZSMcatalyst. Three samples of HZSM-5 with different silica-alumina ratio (SiO2/ Al2O3) of 30, 50 and 70 were prepared and used to investigate the effect of silica-alumina ratio of HZSM-5 to the process. XRD was employed to confirm that the catalyst prepared were HZSM-5. FT-IR analysis for middle range spectra and near range spectra both were engaged to give structural characteristic of the catalyst and to analyze the hydroxyl (OH) groups of the catalyst respectively. The effect of silica-alumina ratio can be seen clearly from the result as HZSM-5 with 30 silica-alumina ratio produced the highest gasoline selectivity compare with the other two catalysts.